Patents for Synthetic Biology: ¿Obsoletes? (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional De Tecnología, Ciencia Y Sociedad, 2019)
Synthetic biology creates living organisms which did not exist in nature. Although it has not achieved an unanimous definition about what it is, its products are a reality and need regulation. There are two major positions regarding its transfer and protection: those who consider that their advances must be patented and those who opt for open access as a means of "protection" and distribution for these advances. The patent system, historically created to protect inanimate inventions, has come to be considered insufficient for synthetic biology. Open access seeks to exchange different inventions to create interchangeable genetic pieces easily and accessible. In such a new science in which a unanimous concensus in its definition is not yet achieved. How it is expected that its protection or transfer can be determined. The solution may not lie in finding the best form of protection within the tools currently granted by intellectual property.